Selected mechanical paremeters of women's hair in the Caucasian population - Skřontová, Marie; Šimkova, Lucie; Bittner, Václav; Chalupa, Bohumil; Zeman, Josef; Jelen, Karel (Neuro endocrinology letters, 2017)
OBJECTIVE: More parameters have been used for more detailed description of mechanical properties of human hair as a fibre than in analogous studies. All measured samples were taken from five different locations on the heads of 60 women of varied age. METHODS: For each hair, the diameter was determined optically and then the test in the Deform Type 2 testing machine was carried out. Deformation curves were obtained by testing 10 mm long samples up to the rupture point at constant temperature, humidity and constant crossbar speed of 2 mm/min. The curves were processed with software for the calculation of mechanical parameters of the hairs. This specialized software has been designed by us for that purpose. Resulting values were arranged into tables and figures. RESULTS: As far as hair cross-section is concerned, it has been found that for the European population it appears to be rather higher - 86 μm - than indicated in formerly published texts. The 56 μm mentioned in the work of other authors has been observed only utterly exceptionally, in 0.3 % of the population. All quantities studied (except extensibility) display moderate to strong positive skewness in comparison to Gauss distribution. The most marked skewness is seen in the resilience. At the same time, this quantity displays the highest value of non-Gaussian distribution. The elasticity module of 2.3±0.6 GPa is three times lower than the one reported by other authors, yet according to the fact published in our work - which shows unambiguously that the thinner the hair, the higher elasticity module it displays - the value of 7.2 GPa for the 56 µm thick hairs is comparable and it confirms the hypothesis that the cortex, which is responsible for the mechanical strength of the hair, is contained in a higher ratio in thinner hairs. This similarly applies to the ultimate strength; the linearity limit is hard to compare with literature, as it almost does not appear there. CONCLUSION: By measuring 886 samples from the heads of 60 adult women of European type, it was possible to ascertain the current norm for a larger number of mechanical parameters of the hairs. Further merit of this work is the fact that the hairs were taken systematically from five well-defined places of the studied heads in equal count, which is an aspect formerly published works do not respect and they do not present the location of sampling.
Keywords: dospělí; Hair; Female; vlasy, chlupy; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Tensile Strength; mechanický stres; Stress, Mechanical; Aged; Young Adult; lidé středního věku; senioři; White People; běloši; Middle Aged; mladiství; pevnost v tahu; Humans